Proceedings of the Twenty-Seventh International Joint Conference on Artificial Intelligence 2018
DOI: 10.24963/ijcai.2018/185
|View full text |Cite
|
Sign up to set email alerts
|

DMC: A Distributed Model Counter

Abstract: We present and evaluate DMC, a distributed model counter for propositional CNF formulae based on the state-of-the-art sequential model counter D4. DMC can take advantage of a (possibly large) number of sequential model counters running on (possibly heterogeneous) computing units spread over a network of computers. For ensuring an efficient workload distribution, the model counting task is shared between the model counters following a policy close to work stealing. The number and the sizes of the messages which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…We also included multi-core solvers dpdb [Fichte et al, 2021b], gpusat2 [Fichte et al, 2019b], as well as countAntom [Burchard et al, 2015]. Note that we excluded distributed solvers such as dCountAntom [Burchard et al, 2016] and DMC [Lagniez et al, 2018] much on the instances. Further, we observed that the employed simple cache as used in Listing 3.1, provides only a marginal improvement.…”
Section: Experimental Results -Hybrid Dynamic Programming In Practicementioning
confidence: 99%
See 1 more Smart Citation
“…We also included multi-core solvers dpdb [Fichte et al, 2021b], gpusat2 [Fichte et al, 2019b], as well as countAntom [Burchard et al, 2015]. Note that we excluded distributed solvers such as dCountAntom [Burchard et al, 2016] and DMC [Lagniez et al, 2018] much on the instances. Further, we observed that the employed simple cache as used in Listing 3.1, provides only a marginal improvement.…”
Section: Experimental Results -Hybrid Dynamic Programming In Practicementioning
confidence: 99%
“…• Counting the number of models of a Boolean formula (#Sat) [Gomes et al, 2009], which recently fostered different applications and solving techniques [Lagniez and Marquis, 2014;Chakraborty et al, 2016;Dueñas-Osorio et al, 2017;Lagniez et al, 2018;Fichte et al, 2018c;Sharma et al, 2019].…”
Section: Introductionmentioning
confidence: 99%
“…For a more ample description of the used techniques, we refer to the model counting competition report [19]. Note that we excluded distributed solvers such as dCountAntom [88] and DMC [89] from our experimental setup. Both solvers require a cluster with access to the OpenMPI framework [90] and fast physical interconnections.…”
Section: Hybrid Dynamic Programming Based On Nested Dpmentioning
confidence: 99%
“…It has been observed by Huang and Darwiche [12] that these tools were implicitly constructing a dec-DNNF equivalent to the input formula. Tools such as c2d [19], D4 [15] or DMC [16] already exploit this connection and have the option to directly output an equivalent dec-DNNF. These solvers explore the set of satisfying assignments by branching on variables of the formula which correspond to a decision node and, when two variable independent components of the formula are detected, compute the number of satisfying assignments of both components and take the product, which corresponds to a decomposable ∧-gate.…”
Section: Proof Systemsmentioning
confidence: 99%